Somatic embryogenesis and plant regeneration from bulb, leaf and root explants of African blue lily (Agapanthus praecox ssp. minimus) - Yaacob, J.S.; Yussof, A.I.M.; Taha, R.M.; Mohajer, S. (2012)
The African blue lily (Agapanthus praecox ssp. minimus) is a valuable plant, reported to contain medicinal compounds such as saponins, sapogenins and phytoecdysteroids, besides gaining popularity as an ornamental and landscape species. This paper reports on high efficiency and rapid in vitro propagation of Agapanthus praecox ssp. minimus via somatic embryogenesis from tissues derived from sterile root, leaf and bulb explants obtained from one-month-old aseptic seedlings of this species. Detailed observations on developmental stages of somatic embryos (from globular to coleoptilar) of this monocotyledonous species were also reported in the present investigation. Friable callus which gave rise to high plant regeneration rate (95) was lucratively produced within 1-2 months after the explants were cultured on Murashige and Skoog (MS) medium supplemented with picloram, 2,4-D, TDZ and combinations of NAA and BAP (0.5 mg/L to 2.0 mg/L). Subsequently, the proliferated calli were transferred onto the same media compositions at 2 weeks interval to encourage extensive production of somatic embryos, followed by transferring to plant growth regulator-free MS medium for complete plant regeneration. Analysis of results showed that explant types highly influenced the degree of response to hormone treatments, whereby root explants were the most responsive. Picloram (a systemic herbicide) was the most effective in inducing somatic embryogenesis from leaf explants, while 2,4-D had excellent influence on root and bulb explants. Further development of somatic embryos to complete plantlets was achieved on MS basal medium. Regenerated plantlets were then hardened and acclimatized on black (peat) soil with 86.67 Â± 6.31 survival rate. Scanning electron microscopic studies on leaf tissues showed no morphological variations between the in vivo and in vitro grown plants, hence mass propagation through tissue culture for true-to-type production of this species is feasible.